Recent Patents on the Structure of Medical Endoscope - Bao, Yu-Dong; Li, Kai; Qi, Dong-Bo; Wen, Wei; Liu, He-Jun (Recent Patents on Engineering, 2022)
Background: The medical endoscope is a major functional component of medical equipment that has become the focus of study around the world. Objective: By comparing and discussing the patents of the medical endoscope, some valuable conclusions have been drawn to predict the future research and development of the medical endoscope. Methods: By analyzing the patent features of the medical endoscope in the mechanical structure, image display, and endoscope system, the function of the medical endoscope on the detection of human internal tissues has been explained. In combination with the key technology of the medical endoscope, related patents have been studied. Results: With the rapid development of technology in the medical industry and the need for practical applications, there is an increase in the requirements for medical endoscopes. Medical endoscopes have undergone a lot of innovations in mechanical structure, imaging, and endoscopic systems. By comparing the characteristics of various patents of medical endoscopes, the main problems of current medical endoscopes, such as complicated structure and poor lighting imaging effect, are analyzed and summarized. The further development trend of medical endoscopes has also been discussed. Conclusion: By improving and optimizing the mechanical structure of the medical endoscope, the lighting method, and the three directions of the system, the performance of the medical endoscope can be improved, and the loopholes in the current technology can be solved. Moreover, it will be more practical.
Keywords: Medical endoscope